Six-armed Goddess - 015 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ The goddess here is holding Shankha and Chakra in the upper hands. In the lower hands a mortar or a bowl, a club, and what looks like a noose.